Universities, Innovation and the Economy - Lawton-Smith, Helen (Routledge Studies in Business Organizations and Networks, 2006)
Universities are increasingly expected to be at the heart of networked structures contributing to society in meaningful and measurable ways through research, the teaching and development of experts, and knowledge innovation. While there is nothing new in universities' links with industry, what is recent is their role as territorial actors. It is government policy in many countries that universities - and in some countries national laboratories - stimulate regional or local economic development. Universities, Innovation and the Economy explores the implications of this expectation. It sites this new role within the context of broader political histories, comparing how countries in Europe and North America have balanced the traditional roles of teaching and research with that of exploitation of research and defining a territorial role. Helen Lawton-Smith highlights how pressure from the state and from industry has produced new paradigms of accountability that